Estimation de la loi de Okun en Algérie à l’aide de modèle ECM - ADOUKA, Lakhdar; BOUGUELL, Zohra (جامعة الوادي University of Eloued, 2013)
ABSTRACT : The objective of this paper is to estimate the Okun’s coefficient, and to check whether the Okun’s law in Algérie is valid or not. For this purpose, we have used annuel time series data during the period 1970-2010. Firstly, I applied difference version of Okun’s law, the Johansen test is employed to find out long run association between unemployment and production, and error correction mechanism (ECM) is used for short run dynamic.
مقال- مجلة رؤى اقتصادية
Keywords: unemployment , production, Okun’s law, cointegration